Analisis Bibliometrik : Mekanisme Aksi dan Efektifitas Flavonoid Terhadap Gagal Ginjal - Mathar, Muhammad Ashhabul Kahfi; Linawati, Ni Made; Wahyuniari, Ida Ayu Ika; Widianti, I Gusti Ayu (Jurnal Ilmu Kedokteran, 2025)
Flavonoids have strong antioxidant properties, which can reduce cell damage that can worsen kidney function. By reducing cellular oxidation, flavonoids help protect the kidneys from damage and inflammation that can lead to kidney failure. In addition, flavonoids also have anti-inflammatory properties to reduce chronic inflammation in the kidneys. Inflammation plays a key role in diseases such as kidney injury, diabetes, asthma, cardiovascular disease and cancer. Diet can affect various stages of inflammation and can have a significant impact on several inflammatory diseases. Increasing scientific evidence suggests that polyphenolic compounds, such as flavonoids, found in fruits, vegetables, nuts, or chocolate, can have anti-inflammatory properties. This reason clearly proves the importance of flavonoid antioxidant activity in inflammation therapy. The method used in this literature review is a bibliometric analysis by searching data through the PubMed database, and Google Scholar and Scopus. The search results of 10 appropriate journals, found that flavonoid compounds can inhibit regulatory enzymes or transcription factors that are important for controlling mediators involved in inflammation.